The Lewis and Clark Expedition - Lawrence, Blythe (Building our nation., 2020)
Briefly chronicles the story of the Lewis and Clark expedition to explore the North American continent and President Jefferson's Louisiana purchase. Includes maps, paintings, photographs of statues, and graphics showcasing the people who went along on the expedition--particularly highlighting Sacagawea--as well as places they visited, as well as a quiz and glossary.